Labour Productivity, ICT and Complementary Factors in the CEE Region - Skorupińska, Aleksandra; Arendt, Łukasz (Olsztyn Economic Journal, 2016)
The paper discusses the role of Information and Communication Technologies for labour productivity in the Central and Eastern European countries, taking into account the consequences of the latest global economic crisis. It focuses on the factors (ICT complementarities) influencing the ICT diffusion trajectories, and thus having impact on labour productivity. The fixed effects models and least squares dummy variable (LSDV) regression was implemented with the use of panel data for 21 European Union member countries. The analysis revealed that only some complementary factors to ICT investments appeared significant to affect labour productivity in the CEE Region. It also showed that sources of labour productivity are sensitive to cyclical changes in the economy.